DETEKSI KEBOCORAN GAS LPG BERBASIS MIKROKONTROLER ATMega8535 - Rusgianto, Rusgianto (Lambung Mangkurat University Press, 2013)
Abstract. An electronic system based on Atmega8535 microcontroller for detectingLPG gas has been done. The system was employed a gas sensor, a temperaturesensor DS18S20, Op-amp LM358, IC voice ISD25120, a microcontroller, and LCDdisplay. The microcontroller was programmed with Basic program that suitable for thedevice. The system was supported a gas sensor and a temperature sensor to get themain signal the gas available on air surrounded gas tube and temperature condition.All of the system was controlled by microcontroller. The signal from the microcontrolleris send to LCD and IC vice ISD 25120. It was concluded that the system work well wellsince the all parameter were displayed on monitor simultaneously.Keywords: ATMega8535, sensor DS18S20, ISD25120